Office Mold Potential: Preparing for Safe Re-Entry after COVID-19 Desertion - Kennedy A. Osakwe; Folusho E. Alamina (Science and Technology - Recent Updates and Future Prospects Vol. 7, 2024)
Background: While workers and organisations heeded lockdown enforcements and abandoned offices in response to the COVID-19 pandemic, the potential for mold growth thrived in unoccupied offices. The growth of mold on buildings has raised concerns and led to increased legal action against property owners, builders, and real estate operators. There is a need to ensure a healthy office environment through health and environmental risk assessment strategies involving the identification and ridding of infective mold which might potentially impact the health of workers. An investigative enquiry to assess the potential and risk of mold exposure is a sine-qua-non to safe re-entry to offices. Materials and Methods: Visual inspection of offices through a walk-through survey was undertaken. An analytical study was conducted through a walk-through survey involving visual inspection, measurement of physico-chemical parameters (Temperature, Relative Humidity, Air Velocity and Particulate Matters PM2.5); and collection and analysis of suspected swabs and bulk samples. Four wall scrapings (bulk) and four swab samples were collected and cultured in the laboratory using nutrient agar. Results: Results showed copious amounts of moisture evidenced by an averagely high relative humidity of 94%, low ambient temperature of 16% and poor ventilation evinced by an air velocity of 0.4 metres per second. Analysis of scrapings and surface swabs revealed the presence of three genus and eight species of fungi in the investigated sites. Analysis of samples of Mucor species revealed (Mucor mucedo, Mucor himalis, Mucor racemosus); Aspergillus species (Aspergillus flavus, Aspergillus fumigatus and Aspergillus terrus); Cladosporium species (Cladosporium cladosproides and Cladosporium sphaerosperum). Conclusion: Poor ventilation, deposits of debris, increased moisture and dysfunctional ventilation system as found in abandoned offices for Mold growth. Post-lockdown re-entry to offices should be preceded by Mold risk assessment among other measures to rule out the presence of Mold growth. Preparations for re-entry should include deep cleaning with anti-Mold agents, optimization of the ventilation system using anti-Mold and High-Efficiency Particulate Absorbing (HEPA) filters, and dehumidifiers and safe remediation of suspected mold growth using suitable personal protective equipment.